2021
DOI: 10.1155/2021/9281961
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Effect of Dental Implants on Jaw Bone under Mechanical and Thermal Loading Conditions

Abstract: Dental implants have been studied over the years to replace missing teeth. One of the conditions for the success of implants is their stability and resistance under the applied forces and minimal tension in the surrounding bone. The purpose of this dissertation is numerical and three-dimensional analysis of jaws with implants under mechanical and thermal loading by the finite element method. For this purpose, implant simulations (including ceramic crown, titanium root, and jaw bone) under dynamic and thermal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The decrease in elastic equivalent strain indicates that the Model B implant undergoes less deformation than the Model A implant. In alignment with the research conducted by Darvish et al [16], the present study similarly observed a reduction in strain corresponding to a decrease in stress. According to the literature, the minimum and maximum equivalent elastic strain amounts should fall within the range of 0.0015 to 0.0030 to create an optimal environment for bone growth without the risk of fracture [6].…”
Section: Strain Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…The decrease in elastic equivalent strain indicates that the Model B implant undergoes less deformation than the Model A implant. In alignment with the research conducted by Darvish et al [16], the present study similarly observed a reduction in strain corresponding to a decrease in stress. According to the literature, the minimum and maximum equivalent elastic strain amounts should fall within the range of 0.0015 to 0.0030 to create an optimal environment for bone growth without the risk of fracture [6].…”
Section: Strain Analysissupporting
confidence: 93%
“…Furthermore, the significant influence of material properties, including elastic modulus, anisotropy, surface properties, and bioactivity on stress values and distribution, was highlighted by FEM analysis results. The importance of supporting the material's long-term functional stability through extensive clinical studies was emphasized [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e application of the finite element method (FEM) has been hugely popular among researchers to analyze the stress distribution of dental implants and the bone surrounding them [18]. FEM is an effective tool which can be used to simulate a complex mechanical problem by disintegrating the 3D problematic geometry into a collection of very small simpler elements [19,20]. Computed tomography is used to obtain the image data, and the corresponding FEM model is generated by the help of a 3D scanner or magnetic resonance imaging [21].…”
Section: Introductionmentioning
confidence: 99%